2021
DOI: 10.1021/acssuschemeng.1c02924
|View full text |Cite
|
Sign up to set email alerts
|

Hydrohydroxymethylation of Ethyl Ricinoleate and Castor Oil

Abstract: The direct functionalization of the carbon–carbon double bonds of castor oil and its derivatives is of major interest to access biosourced building blocks. In particular, polyol derivatives can be produced in this way and find application in the field of bio-based polyesters and polyurethanes. In this study, we described the synthesis of polyhydroxylated derivatives via a hydrohydroxymethylation reaction consisting of two consecutive Rh-catalyzed reactions: a hydroformylation reaction followed by a hydrogenati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…16,17 Rhodium is the most active metal in hydroformylation reactions; hence, most recent investigations focus on rhodium-based systems, typically in combination with tertiary alkylamines. 18–25 In a recent publication from our group, the role and necessary properties of amines in reductive hydroformylation were characterized. 26…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Rhodium is the most active metal in hydroformylation reactions; hence, most recent investigations focus on rhodium-based systems, typically in combination with tertiary alkylamines. 18–25 In a recent publication from our group, the role and necessary properties of amines in reductive hydroformylation were characterized. 26…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic systems based on rhodium are more efficient. More precisely, rhodium catalysts associated with trialkylamines in the presence of CO/H 2 are the more interesting combinations. These processes present some advantages since no oxidable phosphane is used and the two consecutive reactions can take place in the same reactor under the same reaction conditions (catalyst, temperature, pressure). To recover the expensive rhodium catalyst in homogeneous catalytic processes, different approaches were recently developed such as biphasic catalysis (triethanolamine (TEOA) or water as the heavy phase) or a switchable solvent system based on CO 2 . Karakhanov et al reported a biphasic Rh catalytic system for reductive hydroformylation of 1-octene with triethanolamine as the amine ligand and polar phase (ratio N/Rh = 860) .…”
Section: Introductionmentioning
confidence: 99%
“…Likely, this protonated species is incapable of stabilizing the ionic rhodium species, reported as the active catalyst during previous investigations. 21,34,35 Virtually removing the amine from the reaction mixture to switch the phase behavior could explain the deactivation of the catalyst in this experiment.…”
Section: ■ Results and Discussionmentioning
confidence: 86%